Integration of Islam and Social Media:: Instagram Account @fiqihwanita_as Women’s Preaching Medium in the Era of Globalization - Siti Norhidayah; Surawan Surawan; Siti Rahmawati (Bulletin of Islamic Research, 2025)
Globalization has profoundly affected many facets of society, including the dissemination and comprehension of religion. The dynamics of how religious messaging is changing in the digital age, with a focus on how social media—particularly Instagram can effectively spread Islamic teachings. The purpose of this study is to examine how Islam fits into the social media landscape. Specifically, it looks at the Instagram account @fiqihwanita_ as a forum for women's da'wah. This research addresses the impact of Islamic da'wah through social media on women's identity and involvement in the formation of religious narratives while also outlining the strategy and appeal of the account's content. This type of research uses the library research method. A research approach is carried out by collecting information and resources from various types of libraries and written sources. The main goal of library research is to collect relevant data, literature, and knowledge about a particular topic or problem being researched. The research results show that the Instagram account @fiqihwanita_ stands as a dynamic and effective medium for women's da'wah in the era of globalization. Its dynamic content, women-centered approach, and global impact underscore the transformative potential of social media in shaping contemporary religious discourse. The research results are expected to provide insight into how religious messages can be articulated through social media and how Islam can remain authentic and relevant in this digital transformation.